A prophetic word to a prophet : Jonah 4:10-11 as reprimand - Wessels, W. (Journal for semitics, 2007)
Jonah 4:10-11 is a prophetic admonition from Yahweh to the prophet Jonah. Yahweh is reprimanding him for a lack of insight into Yahweh’s grace. The question this article wishes to address is the purpose of the book of Jonah, in particular from the perspective of Jonah 4:10-11. I wish to explore the purpose of the book of Jonah from the perspective of a prophetic admonition to the prophet Jonah in 4:10-11. Jonah is reprimanded for his conviction of how Yahweh’s care and grace should be regarded.,